Early childhood language arts - Jalongo, Mary Renck (Boston : Allyn and Bacon, 2003)
rly Childhood Language Arts' provides instructors with a synthesis of the information on language arts gleaned from research on emergent literacy, early childhood education, and special education. Content and examples enable students to see how children go through the process of acquiring literacy
Includes bibliographical references and index.
Keywords: Language arts (Preschool); Language arts (Early childhood)